Note from the Editor in Chief - Varman, Monica (Consilience, 2011)
It is with great pleasure that I invite you to read the fifth issue of Consilience: the Journal of Sustainable Development. This issue marks another step in our endeavor to provide a platform for interdisciplinary dialogue among diverse, global actors on the topic of sustainable development. I would like to thank the editorial and managing boards of Consilience, and lead senior editor Vighnesh Subramanyan in particular, for the dedication and passion with which they worked on selecting and editing pieces for the journal. This issue preserves and furthers the journal’s mission to further solutions-oriented, open access discourse through a balance of scholarly articles, opinion pieces, field notes, and photo essays. Each piece in this issue challenges the reader to think more broadly, thoroughly, and analytically about sustainable development. As in our previous issues, we have pushed the boundaries of this incredibly complex concept, even going so far as to challenge the very paradigm itself, as author Frances Moore does in the opinion piece “Toppling the Tripod: Sustainable Development, Constructive Ambiguity, and the Environmental Challenge.” This issue features pieces by students, professors, practitioners, and researchers at highly prestigious research institutions across four continents. The content is incredibly diverse, with topics that include access to health care in India, the carbon footprint of Google searches, procurement of clean burning stoves, community based nutrition procurement in Kenya, and the centrality of the democratic process to the pursuit of development. I invite you to engage with the complex questions and challenges raised by our authors, and to bring your own, unique perspective and voice to the conversation. Please feel free to comment on pieces online, attend our events, and explore our other content. Consilience maintains a biweekly editorial column, and will be launching a blog shortly. The blog will act as a platform for more dynamic, time-sensitive coverage of news, events, and opinions in the sustainable development community. We invite you to contribute your reactions to the pieces in our journal to our blog. I am also excited to announce the launch of Sense and Sustainability, a podcast featuring interdisciplinary dialogue on research and policy in the field of sustainable development. It is hosted by Jisung Park, a graduate student studying Economics and Environmental Policy as a Rhodes Scholar at Oxford University. Jisung is a former member of the editorial board of Consilience, and graduated from Columbia University in 2009. The podcast is a collaborative effort with Consilience, and can be accessed from our website. In our ongoing effort to facilitate the exchange of information and perspectives, we have partnered with Field Actions Science Reports (FACTS), an open-access, peer reviewed journal of field actions at Institut Veolia Environnement, to share content and scholarship. Our partnerships and collaborations enable our authors and readers to share best practices and ideas with a wider audience. If you particularly enjoyed the field notes in this issue, I invite you to explore the case studies and field actions examined by FACTS. I hope you enjoy this issue of our journal, and invite you to contribute to the journal through comments, critique, feedback, or submissions at contact@consiliencejournal.org. Yours Sincerely, Monica Varman Editor in Chief Consilience: the Journal of Sustainable Development